PENANGGULANGAN STRES ANAK MELALUI PEMBELAJARAN (PAK) KELAS X DI SMA RK SERDANG MURNI LUBUK PAKAM - Sembiring, Mimpin; Ginting, Rania Betesda Br; Simbolon, Erikson (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
Stress and the management of student stress are crucial issues in the field of education, especially at the high school level. Grade X students at SMA RK Serdang Murni Lubuk Pakam experience academic stress caused by heavy workloads, grade competition, exam anxiety, and uncertainty about their future education. This stress affects students cognitively, affectively, behaviorally, and physiologically, which in turn disrupts their learning process. This study aims to examine how stress is managed among Grade X students and how Catholic Religious Education (PAK) contributes to the coping process. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The subjects were Grade X students and the Catholic Religion teacher. The findings show that stress management is facilitated through spiritual guidance, moral motivation, and reflective activities such as prayer and sharing, led by the PAK teacher. The PAK learning materials, particularly "I Am a Unique Individual" and "Equality between men and women"  help students to know themselves, accept their uniqueness, and build healthy relationships with others and with God. The PAK teacher also acts as a spiritual companion who encourages students to be more open, optimistic, and faithful in facing academic pressures. Thus, Catholic Religious Education has proven to be an effective means of helping students cope with academic stress in the school environment. ABSTRAKStres dan penanggulangan stres siswa merupakan isu penting dalam dunia pendidikan, khususnya di tingkat SMA. Siswa kelas X di SMA RK Serdang Murni Lubuk Pakam mengalami tekanan akademik yang berasal dari banyaknya tugas, persaingan nilai, kecemasan menjelang ujian, serta kebingungan menentukan masa depan. Stres ini berdampak pada aspek kognitif, afektif, perilaku, dan fisiologis siswa yang mengganggu proses belajar mereka. Penelitian ini bertujuan untuk mengetahui bagaimana bentuk penanggulangan stres yang dialami siswa kelas X dan bagaimana pembelajaran Pendidikan Agama Katolik (PAK) berkontribusi dalam proses tersebut. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Subjek penelitian adalah guru PAK dan siswa kelas X. Hasil penelitian menunjukkan bahwa penanggulangan stres dilakukan melalui pendekatan spiritual, motivasi moral, serta kegiatan reflektif dan doa yang dipandu oleh guru PAK. Pembelajaran PAK, khususnya pada materi “Aku Pribadi yang Unik” dan “ kesetaran antara laki-laki dan perempuan” membekali siswa untuk mengenal diri, menerima keunikan mereka, serta membangun relasi yang sehat dengan sesama dan Tuhan. Guru PAK juga memainkan peran sebagai pendamping rohani yang mendorong siswa untuk lebih terbuka, optimis, dan beriman dalam menghadapi tekanan akademik. Dengan demikian, pembelajaran PAK terbukti efektif menjadi sarana penanggulangan stres siswa di lingkungan sekolah.